The role of carbohydrate antigen 19-9 in the clinical evaluation of mature cystic teratomas: an observational study at a tertiary care centre - Manohar, Sumana; S. , Shanaz Nazeen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Carbohydrate antigen (CA) 19-9 is a tumour marker mainly used in the evaluation of gastrointestinal tract malignancies including pancreas, colon and biliary tract. Cases of ovarian tumours such as mucinous neoplasms have been reported to have high levels of CA 19-9. However, its role in the management of cystic teratomas (MCT) which are the most common benign ovarian tumours encountered in gynaecology, is not studied in depth in literature. Methods: In our study, we observed the levels of CA 19-9 in 40 patients presenting with MCT. Its association to the cyst size, contents, laterality and torsion or rupture were documented. Results: The various clinical parameters evaluated in our study such as larger cyst size, presence of torsion and tooth as a content had a positive association with elevated CA 19-9 levels (p<0.05). However, CA 19-9 had no significant relationship with the laterality of the cyst. Thus, CA 19-9 may serve as an important adjunct tool to ultrasonography in the management of dermoid cysts (MCT), particularly in those with larger sizes and at risk of torsion. Conclusions: High levels of CA 19-9 can be observed in benign ovarian tumors like mature cystic teratoma (MCT) and it need not always be associated with malignancy or malignant transformation of benign tumors. Levels more than 100 IU may warrant further imaging studies to rule out gastro-intestinal pathologies. Unnecessary medical investigations or patient anxiety can be avoided in cases of moderate elevation in CA 19-9 levels.